Light-driven reactions in photosynthesis - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Introduction to photosynthesis, Fates of absorbed light, Role of chlorophyll and other pigments, Events in photosystems II and I, Photosynthesis vs. electronic mitochondrial transport, Z-scheme
Reviewed at 2022/11/27